The Yin and Yang of IL-17 in Systemic Sclerosis - Wei, Lanxuan; Abraham, David; Ong, Voon (Frontiers in Immunology, 2022)
IL-17 (IL-17A) is a pro-inflammatory cytokine produced by a sub-set of T helper cells termed Th17 cells primarily in response to cytokines like TGF-β and IL-23 and play an important role in host defense. IL-17 signals via the IL-17RA/RC heterodimer and the adaptor protein Act1 to activate both canonical and non-canonical pathways inducing transcriptional activation and stabilization of mRNAs. IL-17 appears to act not directly on immune cells but stimulates stromal cells such as endothelial and epithelial cells and fibroblasts to secrete other immunomodulatory factors. Fibroblast activated by IL-17 can support the growth and differentiation of immune cells. Studies have begun to uncover a dual role for IL-17; on one hand enhancing immune reactions and promoting inflammatory diseases and on the other decreasing responses and immune activity in established disease settings. The balance of double-edged sword effect of IL-17 and autoimmunity is illustrated in a variety of human diseases and experimental models of diseases. Specifically, the emerging interest in autoimmunity in systemic sclerosis (Scleroderma, SSc) has led to potential role of IL-17A as a target therapy in this disease.